Technogenic geochemical zonation of hydrocarbons as a product of biotransformation - A. P. Khaustov (Известия высших учебных заведений: Геология и разведка, 2016)
Opportunities of the cooperative effects of the interaction of external and internal factors of the hydrocarbon technogenic systems are evaluated. Based on the principles of the self-organization, the opportunities of the manifestation of geochemical zonation forms at the sites of the pollution of the hydrolithosphere with oil and petroleum products are considered. For zones of aeration and saturation the priority in the formation of the technogenic geochemical zonation is given to the organic matter.